Exploring marine microbial diversity: an overview of representative sampling strategies - Ljubešić, Zrinka; Gligora Udovič, Marija; Overlingė, Donata; Grgurević, Filip; Akgül, Füsun; Bacu, Ariola; Díaz-Marrero, Ana R.; Drakulović, Dragana; Fazi, Stefano; Gaudêncio, Susana P.; Kolda, Anamarija; Novoveska, Lucie; et al. (Frontiers in Marine Science, 2025)
The assessment of marine microbial biodiversity is crucial for determining either the environmental status (ecological or biodiversity research) or as a first step in the biodiscovery process (biotechnological research). Regardless of the research purpose, the first step in a biodiversity assessment is sampling, which can range from ad hoc sampling expeditions to long-term monitoring campaigns. In spite of its demands for funds, infrastructure, expertise, equipment, and personnel, sampling is often not adequately planned. This results in increased likelihood for biased sampling, which can lead to misinterpretation of results, omission of valuable specimens and an unrepresentative collection of stored samples, all particularly important for the assessment of microbial biodiversity. For these reasons, we are proposing a conceptual framework to assist in better preparation of sampling, consisting of pre-sampling, sampling and post sampling steps. The manuscript guides the reader through all the necessary steps, regardless of the sampling habitat (from water column to sediment), the sampling techniques and the preservation and storage approaches including culture and biorepositories. Such a harmonized approach can be of benefit for (i) researchers in the field of ecology/biotechnology, (ii) industrial companies requiring information on the providers and availability of data, and (iii) governance structures and funders, in the light of open science principles.